2005
DOI: 10.1261/rna.7430405
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an RNA chaperone function of polypyrimidine tract-binding protein in picornavirus translation

Abstract: The cellular polypyrimidine tract-binding protein (PTB) is recruited by the genomic RNAs of picornaviruses to stimulate translation initiation at their internal ribosome entry site (IRES) elements. We investigated the contribution of the individual RNA recognition motif (RRM) domains of PTB to its interaction with the IRES of foot-and-mouth disease virus (FMDV). Using a native gel system, we found that PTB is a monomer, confirming recent reports that challenged the previous view that PTB is a dimer. Mapping th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 73 publications
(114 reference statements)
6
73
2
Order By: Relevance
“…On the other hand, deletion of RBD3 or RBD4 almost eliminated all stimulation, particularly the RBD4 deletion. The authors concluded that RBDs3 and 4 were sufficient for stimulation (Song et al 2005), in contrast to our conclusions for the EMCV IRES.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, deletion of RBD3 or RBD4 almost eliminated all stimulation, particularly the RBD4 deletion. The authors concluded that RBDs3 and 4 were sufficient for stimulation (Song et al 2005), in contrast to our conclusions for the EMCV IRES.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous report on the stimulation of the FMDV IRES (which is structurally similar to the EMCV core IRES) by PTB deletion mutants found that deletion of RBD1 had no discernible effect (Song et al 2005), and deletion of RBD2, or both RBDs1 and 2, reduced stimulation by <50%, far less than observed here with point mutations inactivating RBD2. On the other hand, deletion of RBD3 or RBD4 almost eliminated all stimulation, particularly the RBD4 deletion.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…2). Several footprinting studies have mapped PTB binding sites on different IRESs and identified several pyrimidine stretches embedded in stem loops and single-stranded regions (in domain K and H of the picornaviruses type II IRESs [50,51], in domain 3 of the hepatitis C virus [52] and also in cellular RNAs [53 -55], see Fig. 2).…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%
“…2). Moreover, reports have shown that interactions between PTB (or the neuronal nPTB) and cellular [56] or viral IRESs [51] are essential for the IRESs to attain their correct functional conformation. Hence, in its interaction with IRES RNAs, PTB acts as an RNA chaperone.…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%